Pre-Mamom Pottery Variation and the Preclassic Origins of the Lowland Maya - Walker, Debra S. (Book collections on Project MUSE., 2022)
"This volume examines the adoption of ceramics in the Maya lowlands, from about 1000 BC, when communities in this region began producing pottery for the first time, until the Mamom ceramic sphere. Unique to lowland Maya experience is that adoption was contemporary with variation in how technology was adapted locally"--